Pengenalan Aplikasi AI Berbasis Web untuk Meningkatkan Minat Belajar Siswa SMA Prayatna terhadap Teknologi Informasi - Indra Sidabutar; Deci Irmayani; Taronisokhi Zebua (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced various aspects of human life, particularly in the field of education. One of the most widely used AI technologies today is ChatGPT, a web-based application capable of assisting users in obtaining information, solving problems, and supporting learning activities through natural language interaction. However, the utilization of ChatGPT as a learning medium among high school students remains limited because many students have not yet understood how to use AI effectively, ethically, and responsibly. Therefore, this Community Service Program aimed to introduce the use of web-based Artificial Intelligence through a case study of ChatGPT as a learning co-pilot in designing a Facebook-inspired Login Page and Home Page using HTML, CSS, and JavaScript. The implementation method consisted of preparation, instructional sessions, demonstrations, hands-on practice, discussions, and evaluations through pre-tests and post-tests. The results of the program indicated that participants were able to understand the basic concepts of Artificial Intelligence, recognize the role of ChatGPT as a learning assistant, develop effective prompts, and create simple web interfaces with AI assistance. Furthermore, the evaluation results demonstrated an improvement in participants' understanding, as reflected by higher average post-test scores compared to pre-test scores. The activity also increased students' interest in information technology and enhanced their awareness that Artificial Intelligence should be utilized as a learning support tool rather than a replacement for human thinking. Overall, this Community Service Program contributed positively to improving students' digital literacy and promoting the responsible use of Artificial Intelligence in educational environments.).